SPEECH ACTS ANALYSIS ON LILLY CONTINO’S COMPLAINT VIDEOS IN A RESTAURANT SETTING - Dewi, Sinta; Astuti, Risa; Nursalam, Hafidatun; Meekaeo, Pisit (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This study examines the use of Speech Acts complaining in Lilly Contino’s misgendering videos. Using Speech Acts categorizations by Searle (1969) and Moon’s (2002) complaining framework, the study aims to identify the strategy of complaints used by Lilly Contino and to examine its effectiveness. The study reveals that Lilly Contino used both implicit and explicit strategies. The implicit strategy used as an initial complaint by using assertive Speech Acts comprises reaffirming, recognizing, and stating, the explicit strategy used as a follow-up complaint by using directive Speech Acts includes demanding and requesting; and the expressive Speech Acts is used as well encompass Lilly’s personal feeling. It is also found that the implicit strategy is less effective for complaints rather than the explicit one. The study furthermore reveals that complaining has its level to address offensive situations. Therefore, this study is particularly useful for understanding the intent of complainers and how the hearer develops a suitable apology.